The Patience Description Of Parents With Children With Disabilities - Putri, Annysa; Hidayat, Ahmad; Muliadi, Rahmad (Journal of Islamic and Contemporary Psychology, 2024)
Parents who have children with disabilities need coping patience. The aim of this study was to find out the description of patience of parents who have children with disabilities. There were 43 research subjects using purposive sampling technique. The data collection method used was the patience scale based on Yusuf's theory (2010). Dealing with the results of research on the level of patience of parents who have children with disabilities at Special Schools (SLB) in Harau district, the majority of parents have a level of patience in the high category, namely 58.1% or a total of 25 people. When it is viewed based on gender, age, income and type of disability, it has indicated that there is no significant difference in the category of patient level.